On the enhanced wear resistance of CoCrFeMnNi high entropy alloy at intermediate temperature. (September 2020) - Joseph, J.; Haghdadi, N.; Annasamy, M.; Kada, S.; Hodgson, P.D.; Barnett, M.R.; Fabijanic, D.M.
Abstract: Sigma (σ) phase precipitation was observed in the recrystallized wear subsurface of a face centred cubic CoCrFeMnNi high entropy alloy after sliding wear at intermediate temperatures (600–800°C). This had a marked effect on the wear resistance of the alloy. The effect of load and temperature on the formation of the wear subsurface microstructure and wear behaviour is studied. The alloy showed excellent wear resistance at an intermediate temperature of 600°C, compared to other testing conditions, due to the formation of a fine-grained wear subsurface along with the precipitation of σ-phase. Graphical abstract: Image, graphical abstract